2023
DOI: 10.1097/mpg.0000000000003766
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Post-ERCP Pancreatitis in Pediatric and Young Adult Patients

Abstract: Objectives: Post-ERCP pancreatitis (PEP) is the most common complication of endoscopic retrograde cholangiopancreatography (ERCP). Limited existing data suggest that prophylactic pancreatic duct (PD) stenting in pediatric patients may increase the risk of PEP. The aim of this study is to identify factors associated with PEP in pediatric patients. Methods: Patients at a single institution who underwent ERCP between 2012 and 2020 were retrospectively reviewed. Patient and procedure-related factors were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In children, retrospective studies have shown efficacy of intravenous ibuprofen 28 and ketorolac 29 in preventing PEP but rectal indomethacin has not been formally evaluated. Surprisingly, a recent retrospective study by Hassan et al 26 in children showed that patients with PEP were more likely to have received rectal indomethacin (OR, 2.1; 95% CI, 1.3-3.2; P = 0.002), but in the high-risk subgroup, no significant difference was found. In our study, rectal indomethacin was administered in all.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In children, retrospective studies have shown efficacy of intravenous ibuprofen 28 and ketorolac 29 in preventing PEP but rectal indomethacin has not been formally evaluated. Surprisingly, a recent retrospective study by Hassan et al 26 in children showed that patients with PEP were more likely to have received rectal indomethacin (OR, 2.1; 95% CI, 1.3-3.2; P = 0.002), but in the high-risk subgroup, no significant difference was found. In our study, rectal indomethacin was administered in all.…”
Section: Discussionmentioning
confidence: 90%
“…4,5 Studies by Troendle et al 4 and Giefer et al 5 in children suggested that prophylactic PD stent placement was associated with an increased risk of PEP. A recent study by Hassan et al, 26 in 736 children undergoing ERCP, reported that PEP occurred more often in the prophylactic PD stent group (OR, 1.8; 95% CI, 1.1-2.95; P = 0.01), although the significance disappeared on subgroup analysis of high-risk patients. The authors have speculated that perhaps pediatric patients are at a higher risk for pancreatic stent-related complications than adults due to age-related physiologic differences.…”
Section: Discussionmentioning
confidence: 94%
“…ESGE has identi ed patient-related risk factors for PEP as suspected sphincter of Oddi dysfunction, female sex, previous pancreatitis, previous PEP, while Procedure-related risk factors include di cult cannulation, pancreatic guidewire passages > 1, and pancreatic injection [4]. A study on children and young adults identi ed factors associated with the development of PEP, including procedural factors such as pancreatic duct injection, cannulation, and sphincterotomy, anatomic factors such as pancreas divisum, complexity scoring, and patient related factors such as a prior history of PEP [12]. The incidence of PEP in the general population is reported to be 3-10% [2], while in our study, the incidence was 14.2%, higher than reported in the literature.…”
Section: Pepmentioning
confidence: 99%
“…Since its introduction in 1968, endoscopic retrograde cholangiopancreatography (ERCP) has evolved into an effective therapeutic modality for pancreaticobiliary disorders. Numerous studies show its safety and efficacy in children 1–10 …”
Section: Introductionmentioning
confidence: 99%